1. The problem statement, all variables and given/known data find dy/dx for x2y+xy2=6 2. Relevant equations 3. The attempt at a solution d/dx (x2y+xy2) = d/dx (6) x2*(dy/dx)+y*2x+x*2y(dy/dx)+2y=0 x2*(dy/dx)+y*2x+x*2y(dy/dx)=-2y (dy/dx)+y*2x+x*2y(dy/dx)=(-2y/x2) (dy/dx)+y*2x+(dy/dx)=(-2y/x2+2xy) I'm not sure what to do now, i know that the answer is (2xy-y2/x2+2xy) I got the denominator correct in my answer but i'm not sure how to get the numerator correctly. Did I go wrong somewhere during the process?